Mapping Geographical Knowledge and Skills Needed for Pre-Service Teachers in Teacher Education - Bourke, Terri; Lidstone, John (SAGE open, 2015)
In Australia, for more than two decades, a “social science” integrated framework was the favored approach for delivering subjects such as history and geography. However, such interdisciplinary approaches have continued to attract criticism from various parts of the academic and public spheres, and since 2009, a return to teaching the disciplines has been heralded as the “new” way forward. Using discourse analysis techniques associated with Foucauldian archeology, the purpose of this article is to examine the Australian Curriculum: Geography document to ascertain the discourses necessary for pre-service teachers to enact effective teaching of geography in a primary setting. Then, based on pre-service teachers’ online survey responses, the article investigates whether such future teachers have the knowledge and skills to interpret, deliver, and enact the new geography curriculum in primary classrooms. Finally, as teacher educators, our interest lies in preparing pre-service teachers effectively for the classroom, so that the findings are used to inform the content of a teacher education course for pre-service primary teachers.